The law of economic surplus in action systems - Witczak, Hubert (Research Papers in Economics and Finance, 2025)
This paper is an attempt to define the law of economic surplus (ES) in action systems (AS). Categories similar to ES are studied in particular by economics, praxeology (forms of efficiency) and management sciences. These sciences attribute the long-term success or failure of AS to various sources, but not directly/mainly to ES. Profit/loss, as forms of positive or negative ES respectively, can be a source of success/failure of AS. These, in turn, have their own sources and conditions.So far, it has been assumed that profit need not be the guiding principle for the management of any (all) AS. None of the scientific theoretical concepts make claims that recognise and solve the broader problem of the sources of longevity of any (all) AS. I try to offer a solution using a praxeological and systemic approach, prognostic-diagnostic methodology and hypothetical-deductive reasoning.I argue that the most important source of longevity is ES. The efficiency of the AS must always be greater than that required to repeat the cycle of action at the initial level and to make the necessary changes. Over the long term, a surplus must be achieved by any (all) AS. (...)